The Impact of Human Capital on Growth : Evidence from West Africa - Brunschwig, Sonia; Sacerdoti, Emilio; Tang, Jon. (Washington, D.C. : International Monetary Fund, 1998)
This paper analyzes the impact of human capital on growth, on the basis of refined calculations of human capital, and with a focus on West Africa. Using a growth-accounting methodology, it distinguishes the sources of growth between the accumulation of factors of production and changes in production intensity or efficiency. Private capital is found to be particularly important to growth, but human capital appears not to be significant. The paper also identifies the terms of trade, trade openness, the government deficit, and the share of government investment in total investment as key policy variables affecting growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet